RISK TAKING BEHAVIOUR MAHASISWA UNIVERSITAS ANDALAS PADANG YANG BERWIRAUSAHA DI MASA PANDEMI COVID-19 - Fitria Rahmi (Jurnal Performa)
During the covid-19 pandemic, the affected workforce was 29,12 million or 14,28%. According to the State Minister for Cooperatives Small and Medium Enterprises, entrepreneurship is the right step to take to survive. Entrepreneurship during a pandemic has many risks, so it takes courage to take risks. About 80% of Andalas University students started entrepreneurship during the pandemic. This study aims to see a picture of risk taking behavior in Andalas University students who are entrepreneurship during the COVID-19 pandemic. In this study, data were obtained from 103 Andalas University students who were entrepreneurs during the COVID-19 pandemic. The measurement is carried out using the risk taking behavior scale from Songan (2006) which consist of 29 items with a reliability of .766 - .871. Based on the results of the stud, it can be said that Andalas University students who were entrepreneurial during the COVID-19 pandemic had a high risk taking behavior of 78,6%. So it can be concluded that Andalas University students who are entrepreneurs during the COVID-19 pandemic have high risk taking behavior